2015
DOI: 10.3390/nu7042719
|View full text |Cite
|
Sign up to set email alerts
|

Consumption and Sources of Dietary Salt in Family Members in Beijing

Abstract: In China, few people are aware of the amount and source of their salt intake. We conducted a survey to investigate the consumption and sources of dietary salt using the “one-week salt estimation method” by weighing cooking salt and major salt-containing food, and estimating salt intake during dining out based on established evidence. Nine hundred and three families (1981 adults and 971 children) with students in eight primary or junior high schools in urban and suburban Beijing were recruited. On average, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 16 publications
3
39
1
Order By: Relevance
“…34 A recent study reported an average salt intake of 15.2 g per day among adults and 10.2 g among seniors in Beijing, China. 35 SMS intervention resulted in an approximately 2 g reduction in salt intake from baseline at 1 and 6 months after the intervention, which is consistent with another health behavioural study conducted in Japan. 19 We also collected the data of fluid intake (presented by IDWG).…”
Section: Discussionsupporting
confidence: 88%
“…34 A recent study reported an average salt intake of 15.2 g per day among adults and 10.2 g among seniors in Beijing, China. 35 SMS intervention resulted in an approximately 2 g reduction in salt intake from baseline at 1 and 6 months after the intervention, which is consistent with another health behavioural study conducted in Japan. 19 We also collected the data of fluid intake (presented by IDWG).…”
Section: Discussionsupporting
confidence: 88%
“…Across the countries, discretionary salt use was high, with 63% of the sample always adding salt during cooking. These responses suggest discretionary salt is a key contributor to salt intake in these countries [40][41][42]. We found a small proportion of participants reported looking at the salt content on food labels (18% overall, 17% of males and 19% of females).…”
Section: Discussionmentioning
confidence: 77%
“…In the community-based salt intake reduction campaign, some people who had the free salt-restriction-spoons did not use it when cooking or did not know how to use it correctly. It has been revealed that 62% of the people got the free spoons but only 45% of the population were actually using it [28]. Chen et al [24] hold a survey to understand the reason why people were not willing to use the spoon, and they found that those people who came from higher socioeconomic classes, had higher education, gained more knowledge about healthy diet, had relatively healthy eating habits were more likely to use salt-restrictionspoons in a correct way, especially for those people who had present hypertension or other NCDs.…”
Section: Intrapersonalmentioning
confidence: 99%
“…Living place is another impact factor of salt consumption, as the cooking habits in a different place would affect the salt and soy sauce amount added in cuisine. It is been reported that rural and suburban population consume more dietary salt than urban population [28]. Married status can also affect people's salt intake, as single people are prone to eat processed food or eat outside rather than cooking at home, which makes it hard to calculate the salt consumption.…”
Section: Intrapersonalmentioning
confidence: 99%